A novel bioassay for thyroid-blocking immunoglobulins - George, Augustine; Lotz, Johannes; Luffy, Maximilian; Ganz, Anna-Lena; Wolf, Jan; Kahaly, George J. (Frontiers in Endocrinology, 2024)
Background Thyroid-blocking immunoglobulins (TBI) are present in 10%–15% of patients with autoimmune thyroid disease (AITD). TBI affect thyroid function. The analytical performance of a novel TBI bioassay was evaluated. Methods Sera from AITD patients were tested with a cell-based TBI reporter bioassay (Thyretain®) with the expression of a luciferase transgene as readout and a new “Turbo™” TBI bioassay with a readout based on a cyclic AMP-activated luciferase. All samples were also run on two TSH-R binding immunoassays. A Passing–Bablok regression, a Bland–Altman plot, and user/lot comparisons were performed. In addition, dose–response curves for Turbo and Thyretain were fitted using serial dilutions, and half-maximal and 80% inhibitory concentrations (IC50/IC80) were compared. Results Of 1,011 unselected AITD patients, 131 patients (212 samples) were TBI positive. Of the 212 samples, 149 (70.3%), 47 (22%), and 16 (7.5%) were hypothyroid, euthyroid, and hyperthyroid, respectively. The three thyrotropin receptor antibody (TSH-R-Ab) assays were negative in 90 controls devoid of autoimmune thyroid disorders. In contrast, the Turbo cyclic adenosine 3′,5′-monophosphate (cAMP) TBI, Thyretain TBI, and the binding assays detected TBI in 212 (100%), 168 (79%), and 138/180 (65%) samples, respectively (p< 0.001). Turbo highly correlated with thyroid function (p< 0.001). The percentage inhibition in both Turbo and Thyretain correlated with TSH-R-Ab binding assay positivity (both p< 0.001). The two bioassays correlated (r = 0.8, p< 0.001), and the Bland–Altman plot displayed no significant bias (0.24). Values scatter with slight systemic deviation between TBI mean values of 10%–50% inhibition, with higher Turbo than Thyretain results. Intra-assay validation demonstrated adequate precision with a very low coefficient of variation (average CV 5.4%) and lower CV with samples with a high inhibitory effect (CVAverage= 1.7% for a sample with 95% inhibition Thyretain). CV did not differ between users (p = 0.35) and lots (p = 0.121). The IC50/IC80 values were 1.55 ng/mL/3.48 ng/mL for Turbo and 6.76 ng/mL/18.46 ng/mL for Thyretain, respectively, demonstrating the markedly higher sensitivity of Turbo. Conclusions The novel, easy-to-perform, rapid, and reliable Turbo TSH-R blocking bioassay detected significantly more TBI than the established immunoassays, emphasizing its higher analytical performance and clinical utility in the management of patients with AITD.